The Impact of Western History on the Evolution of Contemporary Interior Design in India - Sobti, Shaheen; Kapur, Mahima (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The evolution of contemporary interior design in India is deeply intertwined with the country’s encounters with Western history, particularly during colonialism, post-independence modernism, and globalization. This study explores how Western architectural ideologies, spatial planning techniques, and aesthetic preferences have influenced Indian interior spaces over time. The colonial era introduced Victorian, Gothic, and Neoclassical styles, leading to hybrid aesthetics such as Indo-Saracenic and Anglo-Indian designs. Post-independence, Indian modernist architects adopted functional and minimalist approaches inspired by Western modernism, while still grounding their designs in local materials and cultural narratives. Since the 1990s, globalization has accelerated the flow of international styles into Indian homes—ranging from Scandinavian minimalism to industrial chic—reshaping consumer aspirations and spatial arrangements. However, this Western impact did not erase India’s traditional design identity; rather, it fostered a unique fusion of global sensibilities and indigenous practices. The research concludes that the contemporary Indian interior is a product of cultural negotiation—where Western influences are not merely adopted but adapted, recontextualized, and often indigenized, resulting in an eclectic yet cohesive design language reflective of India’s postcolonial identity.